2016
DOI: 10.5152/dir.2016.16123
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced CT- and MRI-based perfusion assessment for pulmonary diseases: basics and clinical applications

Abstract: M agnetic resonance imaging (MRI) is a widely used diagnostic tool for breast imaging in daily practice, with its high sensitivity to detect primary, recurrent, and residual breast cancer. Breast MRI serves as a reliable problem-solving tool in case of inconclusive mammography and ultrasonography (US) findings. It can be used to monitor the results of neoadjuvant chemotherapy and it may also contribute to preoperative evaluation of known lesions. With increasing use of MRI, number of breast lesions visible onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 109 publications
0
20
0
Order By: Relevance
“…During the same period, the parallel imaging technique, as well as fast GRE with short TE or ultra-short TE using contrast media, was proposed for time-resolved (or 4D) contrast-enhanced (CE) MR angiography or dynamic CEperfusion MRI, while investigations were started of velocityencoded (or phase-encoded) MR imaging for pulmonary vascular diseases, as well as thoracic oncology in routine clinical practice. 2,3,18,25,27,28,31 The recently introduced radial acquisition of k-space data from free induction decay (FID) can reduce TE to less than 200 μs, thus minimizing signal decay caused by short transverse relaxation time (T2/T2*). It has, therefore, been suggested that the development of UTE or ZTE sequences could be a game changer for pulmonary MR imaging 32,[43][44][45][46][47][48] because the UTE sequence allows for better visualization of the endogenous MR signal of lung parenchyma than can be obtained with the conventional short echo image sequence.…”
Section: Brief History Of Thoracic Mr Imaging Techniquesmentioning
confidence: 99%
“…During the same period, the parallel imaging technique, as well as fast GRE with short TE or ultra-short TE using contrast media, was proposed for time-resolved (or 4D) contrast-enhanced (CE) MR angiography or dynamic CEperfusion MRI, while investigations were started of velocityencoded (or phase-encoded) MR imaging for pulmonary vascular diseases, as well as thoracic oncology in routine clinical practice. 2,3,18,25,27,28,31 The recently introduced radial acquisition of k-space data from free induction decay (FID) can reduce TE to less than 200 μs, thus minimizing signal decay caused by short transverse relaxation time (T2/T2*). It has, therefore, been suggested that the development of UTE or ZTE sequences could be a game changer for pulmonary MR imaging 32,[43][44][45][46][47][48] because the UTE sequence allows for better visualization of the endogenous MR signal of lung parenchyma than can be obtained with the conventional short echo image sequence.…”
Section: Brief History Of Thoracic Mr Imaging Techniquesmentioning
confidence: 99%
“…However, we use MR angiography in the form of fast dynamic temporally high-resolution MR angiographies of the thorax for a completely different aspect. With time-resolved angiography (time-resolved angiography with stochastic trajectories, or TWIST), the entire lung can be examined in 2-3 s. This makes it possible to identify the optimal contrast medium phase in the lung after the application of contrast medium in the first-pass procedure [23]. In the optimal contrast phase of the lung parenchyma, the non-contrasted areas of the lung can thus be well delimited.…”
Section: General Recommendations For Good Lung Magnetic Resonance Imamentioning
confidence: 99%
“…While CT and MR angiography methods are available, they often require injection of contrast agents and very specific imaging protocols. 91,92 Unlike these methods, CFPA analysis can be done with prior CT scans and does not require contrast agents. CFPA has been validated through preclinical studies, 93,94 and is currently in the process of clinical validation.…”
Section: X-ray Velocimetrymentioning
confidence: 99%